PSYCHOLOGICAL AND PEDAGOGICAL TECHNOLOGIES OF TYUTOR SURVEILLANCE OF CHILDREN WITH HEALTH DISABILITIES - Reznikova, Elena V.; Vasilyeva, Victoria S.; Borodina, Vera A.; Ekzhanova, Elena A.; Solovieva, Irina L. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article is devoted to the psychological and pedagogical support problem of a child with disabilities (HIA) by a teacher-tutor and other support service specialists at the school stage. The aim of the research was the organization of psychological and pedagogical support for students with disabilities in different types of educational organizations and the choice of effective tutorial escort technologies for further successful adaptation in society of children with disabilities. The article considers the features of compiling individual educational routes (IER) for students, the possibility of using effective tutoring technologies in working with children of different nosological groups. The conditions and methods for revealing the personal potential of children with disabilities, possibilities of their individual growth, and other aspects of their adaptation were determined.